Analisis Pelayanan pada Aplikasi Karya Karsa: Memahami Kualitas Layanan dan Pengalaman Pengguna - Riky Apriadi; Rendy Andika; Syahadatillah Syahadatillah; Tata Sutabri (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Karya Karsa application is one of the important platforms in providing diverse services to users in various fields. This article analyzes the quality of services provided by the application with a focus on user satisfaction, ease of use, response from service providers, as well as direct evaluation of user interaction with the application. This research was conducted through an online survey of Karya Karsa application users and direct application usage analysis. The survey results showed the satisfaction of most users with the services provided, but also highlighted areas of improvement related to the user interface that needs to be more intuitive. Analysis of application usage revealed good transaction speed, but showed potential improvements in response to users during peak hours. Recommendations focus on improving the user interface, enhancing the infrastructure and responsiveness of the application, and improving customer support. It is expected that the implementation of these recommendations will improve the service quality and user experience of the Karya Karsa application, strengthening its position as a reliable platform for the community to access the services provided.